Philology And the History of Its Origin (Journal of Pedagogical Inventions and Practices, 2021)
Commonwealth of humanitarian disciplines - linguistic, literary, historical, etc, studying history and clarifying the essence of the spiritual culture of mankind through the linguistic and stylistic analysis of written texts.